THE USE OF MAJUSCULES IN THE BOOK OF TESTIMONIES OF BOJKOVICE 1630-1721 - Filipová, Jitka (Bohemica Olomucensia, 2022)
The paper deals with the issue of capitalization in the handwritten Book of Testimonies of Bojkovice (1630-1721). The author focuses on nouns and adjectives and the evaluation is based on lexical meaning. The results deepen the understanding of the tendencies of the writing of majuscules in manuscripts.
Keywords: Early Modern Czech language; Early Modern manuscripts; Early Modern orthography; capitalization; baroque period; Czech Book of Testimonies; Uherské Hradiště District